Acute Pancreatitis in the View of an Internist - M. Pauliny; M Ondercanin; J. Mackova (Общая реаниматология)
The paper considers the basic principles of the pathophysiology, as well as the diagnosis and treatment of patients with severe acute pancreatitis. Key words: acute pancreatitis, pathophysiology, diagnosis, treatment.